Legal Protection for Creditors in Increasing Satisfaction in Credit Agreements with Liens as Collateral: Perlindungan Hukum Bagi Kreditur Dalam Meningkatkan Kepuasan Dalam Perjanjian Kredit Dengan Hak Gadai Sebagai Jaminan - Chandera Halim; Vincentius Patria Setyawan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The economic and business development in Indonesia heavily relies on the role of financial institutions, particularly banks, in providing capital through credit facilities. However, the distribution of credit also faces the risk of default, necessitating an effective legal protection system for creditors. This research aims to analyze the legal protection for creditors in credit agreements that utilize mortgage rights as collateral under Indonesian positive law, identify the issues that hinder its implementation, and formulate solutions to strengthen legal protection in order to enhance creditor confidence. This study employs a normative legal research method with conceptual and statutory approaches, focusing on an in-depth analysis of creditor protection in credit agreements with mortgage rights through the examination of legal principles, legal systematics, and relevant regulations. Data is collected through literature study, while data analysis is conducted using qualitative methods with a deductive approach, which includes stages of identification, interpretation, consistency analysis, and synthesis to identify legal gaps and formulate recommendations for improving legal protection for creditors. The research findings reveal that legal protection for creditors in credit agreements with mortgage rights in Indonesia faces several obstacles, including inefficient execution processes, limited collateral objects, uncertainty in collateral valuation, low capacity of registration institutions, and a lack of legal awareness among the public. To address these challenges, proposed solutions include optimizing the execution process, expanding the types of collateral objects, establishing clear valuation guidelines, enhancing the capacity of the National Land Agency, providing legal education to the public, improving existing regulations, increasing inter-agency coordination, and strengthening oversight and law enforcement. With these measures in place, it is expected that creditor confidence will improve, the investment climate will enhance, and economic growth will be promoted while maintaining a balance of interests among all parties.